Impact of perception on green purchase intentions and behavior of Vietnamese consumers - Nong , Thi Nhu Mai (Journal of Finance - Marketing Research, 2025)
The research was conducted to understand the influence of perception on green purchase intention and behavior of Vietnamese consumers. The research model was proposed with 08 hypotheses. An integrated approach of qualitative and quantitative methods was employed. Accordingly, with the qualitative method, the study conducted group discussions with 08 consumers who regularly buy green products, were randomly selected to explore and confirm cognitive factors that directly and indirectly affect green purchase intention and behavior. The scales were proposed on the basis of summarizing relevant theories and previous empirical studies. Quantitative research was conducted by surveying 371 consumers to evaluate the reliability of scales as well as to test the research model and proposed research hypotheses by combining PLS-SEM and IPMA. The results show that, except for perception of effectiveness, which does not affect green purchase intention, other factors such as perception of environment, perception of behavioral control, perception of price, and perception of health directly or indirectly influence green purchase intention and behavior. In particular, perception of environment and perception of behavioral control have a great influence on green purchase behavior, but the performance is low, so it needs to be improved. On that basis, the study also proposed some implications to businesses to raise awareness and increase green purchase intention and behavior of consumers in the future, such as coordinating with state management agencies to strengthen communication through green trade promotion activities or applying appropriate management, production, and business operation methods.